Thinking imagination: the city of São Paulo and its geographies - Macedo, Suianni (Geografares, 2014)
In this paper the images produced by the artist Faco Hamburguer, which uses videographic projections through soap bubbles, are taken as a starting point to think about other possible visualities to the São Paulo city. Such images re-exists of the pattern presentation of large urban centers’ landscapes and therefore they create other geographies, smaller geographies, pointing to other possible spatialities. Each image creates other becomings of the space, thinkable spaces, because is at the moment that the image puts in deviation what was usual that the space becoming the unexpected. Discussions about image and imagination and thinking are outlined and is defended an aesthetic education in which what is thought is the act of seeing and not the object seen.Keywords: images; smaller geographies; São Paulo city.